“Spidey Can”: Preliminary Evidence Showing Arachnophobia Symptom Reduction Due to Superhero Movie Exposure - Hoffman, Yaakov S.G.; Pitcho-Prelorentzos, Shani; Ring, Lia; Ben-Ezra, Menachem (Frontiers in Psychiatry, 2019)
Fear of insects, mainly spiders, is considered one of the most common insect phobias. However, to date, no conducted studies have examined the effects of phobic stimuli exposure (spiders/ants) within the positive context of Marvel superheroes movies, such as "Spiderman" or "Antman". A convenience sample of 424 participants divided into four groups watched different clips. Two intervention groups (Spiderman/Antman) and two control groups (Marvel opening/natural scene) were measured twice (pre-post intervention). The measures comprised an online survey assessing socio-demographic variables, familiarity with Marvel movies, comics and phobic symptoms. Reduction in phobic symptoms was significant in the Spiderman and Antman groups in comparison to the control groups. Seven second exposure to insect-specific stimuli within a positive context, reduces the level of phobic symptoms. Incorporating exposure to short scenes from Marvel Cinematic Universe within a therapeutic protocol for such phobias may be robustly efficacious and enhance cooperation and motivation by rendering the therapy as less stigmatic.